2005
DOI: 10.1002/mus.20480
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of histopathologic and molecular pathologic findings in Czech LGMD2A patients

Abstract: Limb-girdle muscular dystrophy type 2A (LGMD2A) is an autosomal-recessive disorder characterized by selective atrophy and progressive weakness of proximal girdle muscles. LGMD2A, the most prevalent form of LGMD, is caused by mutations in the CAPN3 gene that encodes the skeletal muscle-specific member of the calpain family, calpain-3 (p 94). We examined the histopathologic and molecular pathologic findings in 14 Czech LGMD2A patients. Analysis of the CAPN3 gene was performed at the mRNA level, using reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
4
24
0
2
Order By: Relevance
“…This mutation was identified in 6 unrelated LGMD2A patients in our series, and also in several previous reports, where its pathogenetic effects have been suggested [Piluso et al, 2005; Hermanova et al, 2006; Leiden Database], but unsupported by experimental data [Stehlikova et al, 2007; Krahn et al, 2007], or even reported as a polymorphism [Groen et al, 2007; Leiden Database]. …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This mutation was identified in 6 unrelated LGMD2A patients in our series, and also in several previous reports, where its pathogenetic effects have been suggested [Piluso et al, 2005; Hermanova et al, 2006; Leiden Database], but unsupported by experimental data [Stehlikova et al, 2007; Krahn et al, 2007], or even reported as a polymorphism [Groen et al, 2007; Leiden Database]. …”
Section: Resultssupporting
confidence: 81%
“…Furthermore, because of the lack of a molecular proof, some intronic variants have been reported either as polymorphisms or as “possibly pathogenetic”, thus generating confusion and compromising a conclusive genetic counselling. This is the case of the variation c. 1746-20C>G in intron 13 [Hermanova et al, 2006; Stehlikova et al, 2007; Krahn et al, 2007; Groen et al, 2007], for which we have provided a definite demonstration of the pathogenetic effect.…”
Section: Discussionmentioning
confidence: 63%
“…Disruption of proteins in the dysferlin complex can affect the subcellular localization of dysferlin in the absence of mutations in the gene DYSF and may explain the abnormal immunohistochemical results described in the above-mentioned studies [14], [22], [28], [29], [30]. For this reason it is important to quantify dysferlin expression in skeletal muscle WB as well as by IH.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Among the genetically confirmed Czech LGMD-2A patients, a few have been found on histopathology to have neurogenic changes in the muscle biopsy. [15] In one of the Japanese studies, pelvic and shoulder girdle muscle involvement was found to be the most prominent feature. [16] The article by Pathak et al [12] in this issue would be the first authentic report on phenotypic presentation of this Indian LGMD-2A cohort.…”
Section: Department Of Neurology Sanjay Gandhi Postgraduate Institutmentioning
confidence: 97%